Comparative Study of 27-Gauge versus 25-Gauge Vitrectomy for the Treatment of Primary Rhegmatogenous Retinal Detachment - Stanislao Rizzo; Silvio Polizzi; Francesco Barca; Tomaso Caporossi; Gianni Virgili (Journal of Ophthalmology)
Purpose. To compare the vitrectomy time, clinical outcomes, and complications between 27-gauge (27-G) and 25-gauge (25-G) vitrectomy in patients with primary rhegmatogenous retinal detachment (PRRD). Methods. Prospective, nonrandomized, comparative, interventional study. Forty consecutive patients with PRRD were recruited. Twenty patients underwent the 27-gauge procedure and twenty patients had the 25-gauge procedure. The main outcome measure of the study was the actual vitrectomy time. Results. The mean duration of vitreous removal was 23.2 min (SD 6.5) with 27-G vitrectomy and 19.6 min (SD 7.3) with 25-G vitrectomy, resulting in a difference of 3.6 min (95% confidence interval (95%CI): −8.0 to 0.8 mins, p=0.11). Mean logMAR visual acuity improved from 1.70 ± 1.18 preoperatively to 0.12 ± 0.14 at final postoperative visit (p<0.001) in the 27-G group and from 1.52 ± 1.15 preoperatively to 0.22 ± 0.30 at final postoperative visit (p<0.001) in the 25-G group. The anatomical success rate after a single operation was 90.0% and 85.0% in the 27-G and in the 25-G groups (p=0.63), respectively. Intraoperative iatrogenic retinal breaks (IRBs) occurred in 2 eyes in the 27-G group and 1 eye in the 25-G group. Conclusions. Twenty-seven-gauge vitrectomy may be a safe and effective surgery for the treatment of PRRD.